THE TEACHERS’ PROBLEMS ON THE DEVELOPMENT OF BIOLOGY LEARNING MATERIALS THROUGH GUIDED INQUIRY LEARNING MODEL - Makdalena, Rita; Rambitan, Vandalita M M; Palenewen, Evie (Jurnal Penelitian Pendidikan IPA, 2019)
Biology learning in the senior high school level is a subject that needs proof of each sub-material. In order to achieve maximum learning objectives, then the teaching support materials needed to guide the teacher in the learning process. The lacks of the teacher?s ability to develop guided inquiry-based learning materials still dominate. This study aimed to determine the teachers' weakness and the obstacles they faced in the process of preparing and developing the learning materials. The research method used were survey and interviews which included a questionnaire containing the teacher's understanding of the learning materials. As for the results of the study related to the teacher?s understanding of learning materials, 80% of teachers did not understand, and 20% of teachers who understood the learning materials used during the practicum. Then the teachers? obstacles related to developing learning materials, 80% of teachers do not understand how to develop the learning materials and implementing inquiry learning models, and 10% of teachers did not understand how to develop learning materials, and 10% of teachers understand enough to develop guided inquiry-based learning materials. With the problems that lie in the ability of the teacher to develop the learning materials, the need to provide training to the teacher is related to develop learning materials and guiding teachers to develop inquiry-based learning materials.Keywords: learning materials, biology, inquiry